Controllable Optical Properties of Multiple Electromagnetically Induced Transparency in Gaseous Atomic Media - Nguyen Huy, Bang; Le Van, Doai; Dinh Xuan, Khoa (Communications in Physics, 2019)
The advent of electromagnetically induced transparency (EIT) offered a new coherent material with exotic and controllable optical properties. Although, studies on single-EIT are described in detail for single-EIT, however, extension from single- to multi- EIT is currently of current interest due to it gains advantages in multi-channel optical communication, waveguides for optical signal processing and multi-channel quantum information processing. In this work, we review recent research works concerning multi-EIT and some related applications, as controlling group velocity of light, giant Kerr nonlinearity, optical bistability. A special attention of the review also gives for analytical interpretations of EIT spectrum, its dispersion and related applications such as EIT enhanced Kerr nonlinearity and optical bistability to give physics insight. From experimental point of view, a latest development for measuring multi-EIT spectrum and its dispersion in hot medium is presented and compared to theoretical analytical representations.